Review on role of honey in disease prevention and treatment through modulation of biological activities - Rahmani Arshad Husain; Babiker Ali Yousif (Open Life Sciences, 2025)
Honey has been used for centuries due to its health-promoting properties. Honey and its bioactive compounds regulate oxidative stress, inflammation, and other biological activities, making it a promising natural remedy. Its role as anti-diabetic, wound healing, cardioprotective, anti-microbial, and hepatoprotective potential has been proven through in vitro and in vivo studies. Moreover, its role in disease management has been reported through the inhibition of pro-inflammatory enzymes and downregulation of pro-inflammatory cytokine expression and secretion. Besides, it exerts modulatory actions on various signaling pathways such as nuclear factor-κB, tumor suppressor genes, apoptosis, angiogenesis, and MAPK pathway. The main aim of this review is to present a wide-ranging overview of the current evidence regarding the impact of honey on the management of various pathogenic conditions. However, further research based on animal models and clinical trials is required to fully understand the mechanisms of action and safety in the management of various diseases. There is limited clinical data on honey and its mechanisms of action. However, comprehensive clinical studies are needed to fully investigate the potential health benefits of honey, including its efficacies, safety, bioavailability, and underlying mechanisms of action.